Effect of 30 Hz theta burst transcranial magnetic stimulation on the primary motor cortex in children and adolescents - Pedapati, Ernest V.; Gilbert, Donald L.; Horn, Paul S.; Huddleston, David A.; Laue, Cameron S.; Shahana, Nasrin; Wu, Steve W. (Frontiers in Human Neuroscience, 2015)
Fourteen healthy children (13.8±2.2 years, range 10 to 16; M:F=5:9) received 30 Hz intermittent theta burst transcranial magnetic stimulation (iTBS) with a stimulation intensity of 70% of resting motor threshold (RMT) with a total of 300 (iTBS300) pulses. All volunteers were free of neurologic, psychiatric and serious medical illnesses, not taking any neuropsychiatric medications, and did not have any contraindications to Transcranial Magnetic Stimulation. Changes in the mean amplitudes of motor-evoked potentials from baseline following iTBS were expressed as a ratio and assessed from 1 to 10 minutes (BLOCK1) and 1 to 30 minutes (BLOCK2) using repeated-measures analysis of variance. All 14 subjects completed iTBS300 over the dominant primary motor cortex (M1) without any clinically reported adverse events. ITBS300 produced significant M1 facilitation (F5,65=3.165, p=0.01) at BLOCK1 and trend level M1 facilitation at BLOCK2 (F10,129=1.69, p=0.089). Although iTBS300 (stimulation duration of 92 seconds at 70% RMT) delivered over M1 in typically developed children was well-tolerated and produced on average significant facilitatory changes in cortical excitability, the post-iTBS300 neurophysiologic response was variable in our small sample. ITBS300-induced changes may represent a potential neuroplastic biomarker in healthy children and those with neuro-genetic or neuro-psychiatric disorders. However, a larger sample size is needed to address safety and concerns of response variability.